2008
DOI: 10.1063/1.2966690
|View full text |Cite
|
Sign up to set email alerts
|

Inherent paramagnetic defects in layered Si/SiO2 superstructures with Si nanocrystals

Abstract: An extensive electron spin resonance ͑ESR͒ analysis has been carried out on structures comprised of Si nanoparticles ͑ϳ2 nm across͒ embedded in a regular pattern in an amorphous SiO 2 matrix, fabricated by the SiO/ SiO 2 superlattice approach, with the intent to reveal and quantify occurring paramagnetic defects. The as-grown state is found to exhibit only a Si dangling bond ͑DB͒ signal, which through combination of first and second harmonic X-, K-, and Q-band observations in combination with computer spectra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
2

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 101 publications
(47 reference statements)
2
23
2
Order By: Relevance
“…The blue shift for the N 2 annealed samples is often interpreted in literature as a decrease of the size by Si consumption or as influence of the nitrogen hindering the SiO x phase separation and leading to smaller sizes 15. However, as we demonstrated in 13, our findings contradict such an interpretation. We were able to estimate the N incorporation to be in the order of only one monolayer or even less at the interface of the Si NCs.…”
Section: Defect Management For Perfect Sinc/sio2 Interfacescontrasting
confidence: 66%
See 1 more Smart Citation
“…The blue shift for the N 2 annealed samples is often interpreted in literature as a decrease of the size by Si consumption or as influence of the nitrogen hindering the SiO x phase separation and leading to smaller sizes 15. However, as we demonstrated in 13, our findings contradict such an interpretation. We were able to estimate the N incorporation to be in the order of only one monolayer or even less at the interface of the Si NCs.…”
Section: Defect Management For Perfect Sinc/sio2 Interfacescontrasting
confidence: 66%
“…The first one is using the evaporation of SiO powder in a vacuum chamber as described in Ref. 13 resulting in suboxide (SiO ∼1.1 ). The prepared SL are completely free of hydrogen in case of the evaporation process (base pressure of 1 × 10 −6 mbar).…”
Section: Methodsmentioning
confidence: 99%
“…It is worthwhile to stress that we do not exclude the presence of other types of paramagnetic defect states reported in the literature 14–17, which might exist in the SiC and SiO x volumes as well as at the Si/SiO x and SiC/SiO x interfaces for our samples under investigation. We assume that in the case of hydrogenated SiC and SiO x materials containing a high amount of hydrogen, the dangling bond density due to hydrogen out‐diffusion during annealing is likely to dominate the spin density.…”
Section: Discussionmentioning
confidence: 84%
“…32,33 It is suggested that the conflicting effects of the radiative centers and the nonradiative defects result in a moderate increase (a factor $4) in the matrix visible PL intensity, as observed following the postdeposition annealing. Further, the rise in the population of nanoclusters is accompanied with an increase in the density of nonradiative defect centers, such as the asymmetrically relaxed oxygen vacancy or the E 0 center (O 3 :Si), and the Si dangling bond or the P b center (Si 3 :Si).…”
Section: A Matrix-related Luminescence Centersmentioning
confidence: 99%